2013
DOI: 10.5606/tjr.2013.3084
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Generalized Joint Hypermobility and Adhesive Capsulitis of the Shoulder

Abstract: Amaç: Bu çalışmada generalize eklem hipermobilitesi (GEH) ve omzun adeziv kapsüliti (AK) arasındaki muhtemel ilişki araştırıldı. Hastalar ve yöntemler:Çalışma grubunda 120'si AK tanılı ve kontrol grubunda 120'si primer subakromiyal sıkışma sendromu tanılı olmak üzere, toplam 240 hasta çalışmaya dahil edildi. Her iki grupta da ağrı şiddeti, omuz eklem hareket açıklığı, fonksiyonel değerlendirme, engellilik ve hipermobilite değerlendirildi. Generalize eklem hipermobilitesi Beighton skoru, benign eklem hipermobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…For the validity of BS and the association with injuries the validity showed conflicting evidence in three studies (one in children) [Roussel et al, ; Cameron et al, ; Junge et al, ]. For the validity of BS and the association with different diseases (Temporo‐Mandibular Disorders, Chronic Fatigue Syndrome, Adhesive Capsulitis) there was limited positive to conflicting evidence in three studies [Nijs et al, ; Hirsch et al, ; Terzi et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…For the validity of BS and the association with injuries the validity showed conflicting evidence in three studies (one in children) [Roussel et al, ; Cameron et al, ; Junge et al, ]. For the validity of BS and the association with different diseases (Temporo‐Mandibular Disorders, Chronic Fatigue Syndrome, Adhesive Capsulitis) there was limited positive to conflicting evidence in three studies [Nijs et al, ; Hirsch et al, ; Terzi et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to our study, Terzi et al [31] investigated the impact of GJH on the etiopathogenesis of AC, and compared cases with AC and SAIS with respect to JH. They detected lower rates of GJH and BJHS in the AC group, and suggested that GJH might be a protective factor against the development of AC in cases with joint pain.…”
Section: Discussionmentioning
confidence: 63%